2013
DOI: 10.1590/s0104-07072013000400006
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento sobre a Lei 11.108/2005 e a experiência dos acompanhantes junto à mulher no centro obstétrico

Abstract: Pesquisa exploratório-descritiva, com abordagem qualitativa, realizada em uma maternidade pública de Santa Catarina, que objetivou conhecer quais informações os acompanhantes possuem acerca da Lei 11.108/2005, as suas percepções sobre a experiência no centro obstétrico e as ações de apoio junto à mulher. Os dados foram coletados por meio de entrevistas semiestruturadas, de novembro/2010 a maio/2011, com 16 acompanhantes que permaneceram com parturiente durante todos os períodos clínicos do parto. A análise dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 10 publications
1
28
0
11
Order By: Relevance
“…Além disso, reconhecem que sua presença foi importante para que a mulher vivenciasse o momento de forma mais tranquila (3,11) .…”
Section: Introductionunclassified
“…Além disso, reconhecem que sua presença foi importante para que a mulher vivenciasse o momento de forma mais tranquila (3,11) .…”
Section: Introductionunclassified
“…This CSD is closely related to the next CI, since, from the perspective of professionals, the companions are not prepared to face the emotional demands associated with childbirth, causing erroneous ideas about how they will behave. On the other hand, research conducted with companions revealed that the experience in the OC was extremely positive, surpassing negative expectations, despite the lack of preparation (19) . These aspects refer to a reflection on the importance of the professionals to know and value the diversity of feelings, emotions and anxieties involving the companion experience in OC and provide the necessary support (19) .…”
Section: Ci3 -The Companion Does Not Have Emotional and Psychologicalmentioning
confidence: 96%
“…On the other hand, research conducted with companions revealed that the experience in the OC was extremely positive, surpassing negative expectations, despite the lack of preparation (19) . These aspects refer to a reflection on the importance of the professionals to know and value the diversity of feelings, emotions and anxieties involving the companion experience in OC and provide the necessary support (19) . The CSD3 also demonstrates that the health professional tends to allow the companion when he or she considers that the delivery will be "normal", that is, selecting a standard of "ideal delivery" so that the companion may have a good experience.…”
Section: Ci3 -The Companion Does Not Have Emotional and Psychologicalmentioning
confidence: 96%
See 1 more Smart Citation
“…11,108 of 2005 provides women with the right to choose to have a companion in labor, delivery and immediate postpartum in Brazilian health institutions, whether public or private. 4 Often, neglect in this item, compromises the support that the pregnant woman expects at the time of delivery.…”
Section: Introductionmentioning
confidence: 99%